Oxford fabric with high color fastness and preparation method thereof

By using the combined technology of PTT fiber, bamboo charcoal fiber, silk fiber and composite functional agent, high color fastness Oxford fabric was prepared, which solved the problem of Oxford fabric's color decomposition and color change under ultraviolet light, and achieved good color fixation effect and UV protection.

CN119243393APending Publication Date: 2025-01-03HANGZHOU FENGDE TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422194.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing Oxford fabrics lack protection function under ultraviolet light exposure, and the color lake is prone to decomposition and causes color light to change, affecting the beauty and durability of the fabric.

Method used

PTT fiber, bamboo charcoal fiber, silk fiber, sodium sulfate, sodium carbonate and composite functional agents are used as raw materials to prepare high color fastness Oxford fabrics through winding, warping, dyeing and impregnation processes. The composite functional agent contains quaternary ammonium salt Structure and benzophenone structure can form ionic bonds and absorb ultraviolet light.

Benefits of technology

It improves the color fixation effect, ultraviolet light protection and antibacterial properties of Oxford fabrics, extends the durability of the fabric, solves the problems of color lake decomposition and color light change, and improves the overall performance of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to an oxford fabric with high color fastness and a preparation method thereof, and belongs to the technical field of textiles. Comprising the following raw materials in parts by mass: 55-68 parts of PTT fibers, 25-30 parts of bamboo charcoal fibers, 15-18 parts of silk fibers, 5-6 parts of sodium sulfate, 0.3-0.5 part of sodium carbonate and 0.6-1.3 parts of a composite functional agent, the preparation method comprises the following steps: firstly, preparing short fibers from PTT fibers, bamboo charcoal fibers and silk fibers, weaving the short fibers into an oxford spinning blank after spinning, spooling, twisting, scaling, warping and denting, and then dyeing, fixing and drying the oxford spinning blank to obtain the high-color-fastness oxford fabric. The prepared oxford fabric is soft, comfortable, high in toughness, bright in color and luster and good in color fixing effect, has good absorptivity on ultraviolet light, has an antibacterial effect and can be widely applied to the fields of clothes and home textiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textiles, and in particular relates to an Oxford fabric with high color fastness and a preparation method thereof. Background Art

[0002] Oxford fabric originated in the UK. It was named after the cotton fabric used in the student uniform shirts of Oxford University. Oxford fabric is mainly made of cotton yarn and polyester fiber (polyester) cross-woven. This combination makes Oxford fabric have the hygroscopicity and comfort of cotton, and the wear resistance and wrinkle resistance of polyester. Today, the development of Oxford fabric has become more mature, with the characteristics of easy washing and quick drying, soft feel, good hygroscopicity, and comfortable wearing. Not only that, Oxford fabric also has excellent wear resistance, fall resistance, and pressure resistance. These properties enable Oxford fabric to maintain excellent performance in various application scenarios. In the clothing industry, Oxford fabric is widely used to make shirts, sportswear, etc.; in the outdoor products industry, it is used to make suitcases, backpacks, tents, etc. In addition, Oxford fabric can also be used to make automotive interiors, furniture fabrics and other fields.

[0003] However, the Oxford fabric in the prior art still has the disadvantage of poor color fixing effect and lacks ultraviolet light protection effect. Under ultraviolet light irradiation conditions, conventional Oxford fabric not only lacks the protection function for the human body, but the color lake on the fabric is also easily decomposed, resulting in color change problems, affecting the appearance of the fabric. This is an urgent problem that needs to be solved in the prior art defects of Oxford fabric. Summary of the invention

[0004] The object of the present invention is to provide an Oxford fabric with high color fastness and a preparation method thereof, so as to solve the problems mentioned in the above background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high color fastness Oxford fabric comprises the following raw materials in parts by weight: 55-68 parts of PTT fiber, 25-30 parts of bamboo charcoal fiber, 15-18 parts of silk fiber, 5-6 parts of sodium sulfate, 0.3-0.5 parts of sodium carbonate, and 0.6-1.3 parts of a composite functional agent; A method for preparing an Oxford fabric with high color fastness comprises the following steps: The first step: weigh the raw materials according to the mass proportions of PTT fiber 55-68 parts, bamboo charcoal fiber 25-30 parts, silk fiber 15-18 parts, sodium sulfate 5-6 parts, sodium carbonate 0.3-0.5 parts, and composite functional agent 0.6-1.3 parts, make the PTT fiber, bamboo charcoal fiber, and silk fiber into short fibers, and then use a high-speed winding machine to wind the short fibers, and after winding, use a double twisting machine to twist and shrink them for standby use; Step 2: The bobbins that have been shrunk in the first step are warped by a sectional warping machine, and then reeded to weave the Oxford spinning blank; Step 3: dissolving the composite functional agent and sodium carbonate in deionized water to obtain a post-treatment solution; Step 4: The Oxford spun fabric in the second step is put into the dyeing vat after being desized, and sodium sulfate is added to the dyeing vat, and the temperature is continuously raised to complete the dyeing; Step 5: Immerse the dyed Oxford fabric in a post-treatment solution, and dry it after immersion to obtain an Oxford fabric with high color fastness.

[0006] Furthermore, the winding speed in the first step is 380-460 m / min, and the winding tension is set to 0.06-0.08N.

[0007] Furthermore, the twisting speed of the two-for-one twisting machine in the first step is 7800-8600 r / min, and the twisting twist is 6-8 twists / cm.

[0008] Furthermore, the warping speed of the Oxford fabric in the second step is 80-120 m / min.

[0009] Furthermore, in the second step, the warp density of the Oxford fabric is 90-105 strands / cm, and the weft density is 40-55 strands / cm.

[0010] Furthermore, in the fourth step, the dyeing temperature condition is 70-90° C., and the dyeing time condition is 30-45 min.

[0011] Furthermore, in the fifth step, the temperature condition of the immersion treatment is 60-70° C., and the time condition of the immersion treatment is 30-60 min.

[0012] Furthermore, the drying temperature in the fifth step is 130°C.

[0013] Furthermore, the composite functional agent is prepared by the following steps: Step 1: 3,5-dihydroxytoluene, aluminum chloride and carbon tetrachloride are mixed in a stainless steel reactor, a condenser and a thermometer are installed, magnetic stirring is turned on, the system temperature is raised to 60-70°C, 2-hydroxybenzoyl chloride is added dropwise to the stainless steel reactor, and after the addition is completed, the reaction is carried out at a temperature of 150-160°C for 4-6 hours. After the reaction is completed, deionized water is added to the stainless steel reactor, and the organic layer is separated by a separatory funnel, and then the intermediate 1 is obtained by rotary evaporation; Step 2: Mix the intermediate 1, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 70-75°C for 12-16 hours. After the reaction is completed, add deionized water to the three-necked flask, separate the organic layer with a separatory funnel, and then rotary evaporate to obtain the intermediate 2; Step 3: Mix the intermediate 2, diallylmethylamine and carbon tetrachloride in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 60-70°C for 6-8h. After the reaction is completed, rotary evaporation is performed to obtain the intermediate 3; Step 4: Mix pyridine, 4-chlorobutene and carbon tetrachloride in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 65-75°C for 4-6 hours. After the reaction is completed, rotary evaporation is performed to obtain intermediate 4; Step 5: Mix intermediate 3, intermediate 4, diallylmethylamine, tetrasodium ethylenediaminetetraacetate, and deionized water in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, use glacial acetic acid to adjust the system pH to 7, then raise the system temperature to 70-75°C, and add tetrasodium ethylenediaminetetraacetate to the three-necked flask again. After the addition is completed, react at a temperature of 70-75°C for 3-4h. After the reaction is completed, add deionized water to the three-necked flask for washing, and rotary evaporate to obtain the composite functional agent; Furthermore, the amount ratio of 3,5-dihydroxytoluene, aluminum chloride, carbon tetrachloride and 2-hydroxybenzoyl chloride used in step 1 is 0.1 mol: 22-24 g: 60-80 mL: 0.1 mol.

[0014] Furthermore, the amount ratio of intermediate 1, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride used in step 2 is 0.05 mol: 0.05-0.07 mol: 5-7 g: 100-120 mL.

[0015] Furthermore, the amount ratio of the intermediate 2, diallylmethylamine and carbon tetrachloride used in step 3 is 0.04 mol: 0.05-0.06 mol: 80-100 ml.

[0016] Furthermore, the amount ratio of pyridine, 4-chlorobutene and carbon tetrachloride used in step 4 is 0.05 mol:0.05 mol:60-80 mL.

[0017] Furthermore, the dosage ratio of intermediate 3, intermediate 4, diallylmethylamine, tetrasodium ethylenediaminetetraacetate, and deionized water used in step 5 is 0.01 mol: 0.01 mol: 0.02-0.03 mol: 0.03 g: 40 g; wherein the ratio of tetrasodium ethylenediaminetetraacetate added for the first time to tetrasodium tetraacetate added for the second time is 1:2.

[0018] Beneficial effects of the present invention: The invention uses PTT fiber, bamboo charcoal fiber, silk fiber, sodium sulfate, sodium carbonate and a composite functional agent as raw materials to prepare an Oxford fabric with high color fastness. The invention prepares short fibers from PTT fiber, bamboo charcoal fiber and silk fiber, weaves the short fibers into Oxford spinning embryos through spinning, winding, twisting, shrinking, warping and reeding, and then dyes, fixes and dries the Oxford spinning embryos to obtain the Oxford fabric with high color fastness. Three kinds of fibers are selected from the raw materials of the Oxford fabric for mixed winding, and the prepared Oxford fabric is soft and comfortable and has stronger toughness. In addition, the invention adds sodium sulfate during dyeing, and the coloring effect is greatly improved. The post-treatment liquid prepared by using sodium carbonate and the composite functional agent is used for color fixing treatment, and the finally prepared Oxford fabric is comfortable and skin-friendly, bright in color and has good color fixing effect.

[0019] The present invention uses 3,5-dihydroxytoluene and 2-hydroxybenzoyl chloride as raw materials, aluminum chloride as a catalyst, and performs Fries rearrangement to obtain an intermediate 1, and then uses the intermediate 1 as a raw material, N-succinimide as a halogenating agent, and benzoyl peroxide as an initiator to carry out a substitution reaction at the benzyl position of the intermediate 1 to carry a bromine atom to obtain an intermediate 2, and then the bromine atom of the intermediate 2 and the tertiary amine part of diallylmethylamine undergo a quaternary ammonium salt reaction to obtain an intermediate 3. At the same time, the present invention uses pyridine and 4-chlorobutene as raw materials to obtain an intermediate 4 through a quaternary ammonium salt reaction, and finally copolymerizes the intermediate 3, the intermediate 4, and diallylmethylamine under the action of a chelating agent, tetrasodium ethylenediaminetetraacetate, to obtain a composite functional agent; the composite functional agent itself is a macromolecular linear fiber structure, which is similar to the fiber structure of Oxford fabrics, and can play a good role on Oxford fabrics, and the composite functional agent contains a large number of quaternary ammonium salt structure cations The group can form an ionic bond with the anionic part of the dye to form a lake, so it can have a good color fixing effect. In addition, the composite functional agent also has a benzophenone structure, and the carbonyl group has multiple phenolic hydroxyl groups. When exposed to ultraviolet light, the carbonyl group of the composite functional agent can form an intramolecular hydrogen bond with the adjacent hydroxyl group to absorb ultraviolet light, turn itself into an excited state and release the energy of ultraviolet light in the form of heat energy. Therefore, it has a good absorption effect on ultraviolet light and has strong self-stability. Thanks to the macromolecular linear fiber structure of the composite functional agent, this ultraviolet light absorption effect is long-lasting and not easy to lose effectiveness due to washing. It can greatly improve the ultraviolet protection effect and durability of Oxford fabrics, and solve the problem of lake decomposition and color change caused by sunlight on Oxford fabrics, further improving the color fixing effect of Oxford fabrics. Not only that, the pyridine group in the composite functional agent can also give Oxford fabrics good antibacterial properties.

[0020] The high color fastness Oxford fabric preparation process of the invention is safe and environmentally friendly, does not contain harmful substances such as formaldehyde, and the prepared Oxford fabric is soft and comfortable, has strong toughness, bright color, good color fixing effect, good ultraviolet light absorption, and has antibacterial effect, and can be widely used in the field of clothing and home textiles. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0022] A composite functional agent is prepared by the following steps: Step 1: 0.1 mol 3,5-dihydroxytoluene, 22 g aluminum chloride and 60 mL carbon tetrachloride were mixed in a container, stirred evenly, the system temperature was raised to 60°C, 0.1 mol 2-hydroxybenzoyl chloride was added dropwise to the container, and after the addition was completed, the reaction was carried out at a temperature of 150°C for 4 hours. After the reaction was completed, deionized water was added to the container, and the organic layer was separated and then rotary evaporated to obtain intermediate 1; Step 2: 0.05 mol of intermediate 1, 0.05 mol of N-bromosuccinimide, 5 g of benzoyl peroxide, and 100 mL of carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 70° C. for 12 h. After the reaction was completed, deionized water was added to the container, and the organic layer was separated and rotary evaporated to obtain intermediate 2; Step 3: 0.04 mol of intermediate 2, 0.05 mol of diallylmethylamine and 80 mL of carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 60-70°C for 6 hours. After the reaction was completed, intermediate 3 was obtained by rotary evaporation; Step 4: 0.05 mol pyridine, 0.05 mol 4-chlorobutene and 60 mL carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 65°C for 4 h. After the reaction was completed, the intermediate 4 was obtained by rotary evaporation; Step 5: 0.01 mol of intermediate 3, 0.01 mol of intermediate 4, 0.02 mol of diallylmethylamine, 0.01 g of tetrasodium ethylenediaminetetraacetate, and 40 g of deionized water are mixed in a container, stirred evenly, and the pH value of the system is adjusted to 7 with glacial acetic acid. Then, the temperature of the system is raised to 70°C, and 0.02 g of tetrasodium ethylenediaminetetraacetate is added to the container again. After the addition is completed, the reaction is carried out at a temperature of 70°C for 3 hours. After the reaction is completed, deionized water is added to the container for washing, and the composite functional agent is obtained by rotary evaporation. Example

[0023] A composite functional agent is prepared by the following steps: Step 1: 0.1 mol 3,5-dihydroxytoluene, 23 g aluminum chloride and 70 mL carbon tetrachloride were mixed in a container, stirred evenly, the system temperature was raised to 65°C, 0.1 mol 2-hydroxybenzoyl chloride was added dropwise to the container, and after the addition was completed, the reaction was carried out at a temperature of 155°C for 5 hours. After the reaction was completed, deionized water was added to the container, and the organic layer was separated and then rotary evaporated to obtain intermediate 1; Step 2: 0.05 mol of intermediate 1, 0.06 mol of N-bromosuccinimide, 6 g of benzoyl peroxide, and 110 mL of carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 73°C for 14 h. After the reaction was completed, deionized water was added to the container, and the organic layer was separated and rotary evaporated to obtain intermediate 2; Step 3: 0.04 mol of intermediate 2, 0.055 mol of diallylmethylamine and 90 mL of carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 65°C for 7 h. After the reaction was completed, intermediate 3 was obtained by rotary evaporation; Step 4: 0.05 mol pyridine, 0.05 mol 4-chlorobutene and 70 mL carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 70°C for 5 h. After the reaction was completed, the intermediate 4 was obtained by rotary evaporation; Step 5: Mix 0.01 mol of intermediate 3, 0.01 mol of intermediate 4, 0.025 mol of diallylmethylamine, 0.01 g of tetrasodium ethylenediaminetetraacetate, and 40 g of deionized water in a container, stir evenly, adjust the system pH to 7 with glacial acetic acid, then raise the system temperature to 73°C, and add 0.02 g of tetrasodium ethylenediaminetetraacetate to the container again. After the addition is completed, react at a temperature of 73°C for 3.4 hours. After the reaction is completed, add deionized water to the container for washing, and rotary evaporate to obtain the composite functional agent. Example

[0024] A composite functional agent is prepared by the following steps: Step 1: 0.1 mol 3,5-dihydroxytoluene, 24 g aluminum chloride and 80 mL carbon tetrachloride were mixed in a container, stirred evenly, the system temperature was raised to 70°C, 0.1 mol 2-hydroxybenzoyl chloride was added dropwise to the container, and after the addition was completed, the reaction was carried out at a temperature of 160°C for 6 hours. After the reaction was completed, deionized water was added to the container, and the organic layer was separated and then rotary evaporated to obtain intermediate 1; Step 2: 0.05 mol of intermediate 1, 0.07 mol of N-bromosuccinimide, 7 g of benzoyl peroxide, and 120 mL of carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 75°C for 16 h. After the reaction was completed, deionized water was added to the container, and the organic layer was separated and rotary evaporated to obtain intermediate 2; Step 3: 0.04 mol of intermediate 2, 0.06 mol of diallylmethylamine and 100 mL of carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 70°C for 8 h. After the reaction was completed, intermediate 3 was obtained by rotary evaporation; Step 4: 0.05 mol pyridine, 0.05 mol 4-chlorobutene and 80 mL carbon tetrachloride were mixed in a container, stirred evenly, and reacted at 75°C for 6 h. After the reaction was completed, the intermediate 4 was obtained by rotary evaporation; Step 5: 0.01 mol of intermediate 3, 0.01 mol of intermediate 4, 0.03 mol of diallylmethylamine, 0.01 g of tetrasodium ethylenediaminetetraacetate, and 40 g of deionized water are mixed in a container, stirred evenly, and the pH of the system is adjusted to 7 with glacial acetic acid. The system temperature is then raised to 75°C, and 0.02 g of tetrasodium ethylenediaminetetraacetate is added to the container again. After the addition is completed, the reaction is carried out at a temperature of 75°C for 4 hours. After the reaction is completed, deionized water is added to the container for washing, and the composite functional agent is obtained by rotary evaporation.

[0025] Comparative Example 1 This comparative example is a UV absorber sold by Lianlong New Materials Co., Ltd.

[0026] The composite functional agent obtained in Examples 1-3 and the commercially available ultraviolet absorber of Comparative Example 1 were coated on wooden boards, and a wooden board not coated with any substance was used as a blank control. Five wooden boards were placed in a test box and subjected to ultraviolet aging test at a temperature of 80°C and 4h ultraviolet irradiation conditions, wherein the test wavelength of ultraviolet light was QUVB (280-320nm) and the intensity was 0.81W / m 2 The yellowing value standard is tested according to the national standard GB11186.3-89. The test results are shown in Table 1:

[0027] It can be seen from Table 1 that the change in the yellowness value of the wood board coated with the composite functional agent is much smaller than the change in the yellowness value of the wood board coated with the commercially available ultraviolet absorber, indicating that the composite functional agent of the present invention can absorb ultraviolet light well, has good durability and lasting effect, and will not decompose and denature under long-term high-intensity ultraviolet light irradiation conditions. The use of the composite functional agent in the Oxford fabric can effectively improve the durability and ultraviolet protection of the Oxford fabric. Example

[0028] A high color fastness Oxford fabric comprises the following raw materials in parts by weight: 55 parts of PTT fiber, 30 parts of bamboo charcoal fiber, 18 parts of silk fiber, 6 parts of sodium sulfate, 0.5 parts of sodium carbonate, and 1.3 parts of the composite functional agent obtained in Example 1; A method for preparing an Oxford fabric with high color fastness comprises the following steps: The first step: weigh each raw material by mass: 55 parts of PTT fiber, 30 parts of bamboo charcoal fiber, 18 parts of silk fiber, 6 parts of sodium sulfate, 0.5 parts of sodium carbonate, and 1.3 parts of the composite functional agent obtained in Example 1, and make the PTT fiber, bamboo charcoal fiber, and silk fiber into short fibers, and spin the short fibers, and then use a high-speed winder for winding treatment, the winding speed is 380m / min, the winding tension is 0.06N, and after winding, it is twisted with a double twister and then shrunk for standby use, the twisting speed is 7800r / min, and the twisting twist is 6 twists / cm; Step 2: The yarn that has been shrunk in the first step is warped by a slitting warping machine at a warping speed of 80 m / min, and then reeded to weave the Oxford spinning blank. The warp density is 90 strands / cm and the weft density is 40 strands / cm; Step 3: dissolving the composite functional agent and sodium carbonate obtained in Example 1 with deionized water to obtain a post-treatment solution; Step 4: The Oxford spun fabric in the second step is put into the dyeing vat after being desized, and sodium sulfate is added to the dyeing vat, and the temperature is continuously raised to 70°C and kept for 30 minutes to complete the dyeing; Step 5: Immerse the dyed Oxford fabric in a post-treatment solution at 60°C, immerse for 30 minutes, and then dry at 130°C to obtain an Oxford fabric with high color fastness. Example

[0029] A high color fastness Oxford fabric comprises the following raw materials in parts by weight: 62 parts of PTT fiber, 27 parts of bamboo charcoal fiber, 15 parts of silk fiber, 5.5 parts of sodium sulfate, 0.4 parts of sodium carbonate, and 1.1 parts of the composite functional agent obtained in Example 2; A method for preparing an Oxford fabric with high color fastness comprises the following steps: The first step: weigh each raw material by mass: 62 parts of PTT fiber, 27 parts of bamboo charcoal fiber, 15 parts of silk fiber, 5.5 parts of sodium sulfate, 0.4 parts of sodium carbonate, and 1.1 parts of the composite functional agent obtained in Example 2, and make the PTT fiber, bamboo charcoal fiber, and silk fiber into short fibers, and spin the short fibers, and then use a high-speed winder for winding treatment, the winding speed is 420m / min, the winding tension is 0.07N, and after winding, the winding machine is twisted and then shrunk for standby use, the twisting speed is 8200r / min, and the twisting twist is 7 twists / cm; Step 2: The yarn that has been shrunk in the first step is warped by a slitting warping machine at a warping speed of 100 m / min, and then reeded to weave the Oxford spinning blank, with a warp density of 98 strands / cm and a weft density of 48 strands / cm; Step 3: dissolving the composite functional agent and sodium carbonate obtained in Example 2 with deionized water to obtain a post-treatment solution; Step 4: The Oxford spun fabric in the second step is put into the dyeing vat after being desized, and sodium sulfate is added to the dyeing vat, and the temperature is continuously raised to 80°C and kept for 38 minutes to complete the dyeing; Step 5: Immerse the dyed Oxford fabric in a post-treatment solution at 65°C, immerse for 45 minutes, and then dry at 130°C to obtain an Oxford fabric with high color fastness. Example

[0030] A high color fastness Oxford fabric comprises the following raw materials in parts by weight: 68 parts of PTT fiber, 25 parts of bamboo charcoal fiber, 15 parts of silk fiber, 5 parts of sodium sulfate, 0.4 parts of sodium carbonate, and 0.6 parts of the composite functional agent obtained in Example 3; A method for preparing an Oxford fabric with high color fastness comprises the following steps: The first step: weigh each raw material by mass: 68 parts of PTT fiber, 25 parts of bamboo charcoal fiber, 15 parts of silk fiber, 5 parts of sodium sulfate, 0.4 parts of sodium carbonate, and 0.6 parts of the composite functional agent obtained in Example 3, make the PTT fiber, bamboo charcoal fiber, and silk fiber into short fibers, and spin the short fibers, and then use a high-speed winder for winding treatment, the winding speed is 460m / min, the winding tension is 0.08N, and after winding, the winding machine is twisted and then shrunk for standby use, the twisting speed is 8600r / min, and the twisting twist is 8 twists / cm; Step 2: The yarn that has been shrunk in the first step is warped with a slitting warping machine at a warping speed of 120 m / min, and then reeded to weave the Oxford spinning blank, with a warp density of 105 strands / cm and a weft density of 55 strands / cm; Step 3: dissolving the composite functional agent and sodium carbonate obtained in Example 3 with deionized water to obtain a post-treatment solution; Step 4: The Oxford spun fabric in the second step is put into the dyeing vat after being desized, and sodium sulfate is added to the dyeing vat, and the temperature is continuously raised to 90°C and kept for 45 minutes to complete the dyeing; Step 5: Immerse the dyed Oxford fabric in a post-treatment solution at 70°C, immerse for 60 minutes, and then dry at 130°C to obtain an Oxford fabric with high color fastness.

[0031] Comparative Example 2 The "composite functional agent obtained in Example 3" used in Example 6 was removed, and the other raw materials and steps remained unchanged.

[0032] Comparative Example 3 This comparative example is the Oxford fabric sold by Suzhou Shengshuangxiang Textile Technology Co., Ltd.

[0033] The Oxford fabrics with high color fastness obtained in Examples 4-6 and Comparative Example 2 and the commercially available Oxford fabrics in Comparative Example 3 were placed on a workbench and rubbed 25 times at a high speed with a force of 15N, and then the color fastness was evaluated according to the evaluation method of the national standard GB / T 3920-2008. The test results are shown in Table 2:

[0034] It can be seen from Table 2 that the Oxford fabric prepared by the preparation method of the present invention has good color fastness to friction, and can generally reach level 5 color fastness, which is much better than the commercially available Oxford fabric. In Comparative Example 2, since the composite functional agent of the present invention is not used, the color fastness of the Oxford fabric prepared is still poor, indicating that the composite functional agent of the present invention can effectively improve the color fastness of the Oxford fabric; in summary, the Oxford fabric of the present invention has good color fastness and ultraviolet protection effect, is soft and skin-friendly, and can be widely used in the fields of clothing and home textiles.

[0035] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An Oxford fabric with high color fastness, characterized in that: The invention comprises the following raw materials in parts by weight: 55-68 parts of PTT fiber, 25-30 parts of bamboo charcoal fiber, 15-18 parts of silk fiber, 5-6 parts of sodium sulfate, 0.3-0.5 parts of sodium carbonate, and 0.6-1.3 parts of composite functional agent; Wherein, the composite functional agent is prepared by the following steps: Step 1: 3,5-dihydroxytoluene, aluminum chloride and carbon tetrachloride are mixed in a container, stirred evenly and the system temperature is raised to 60-70°C, then 2-hydroxybenzoyl chloride is added to the container, and after the addition is complete, the mixture is reacted at a temperature of 150-160°C for 4-6 hours to obtain intermediate 1; Step 2: Mix intermediate 1, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride in a container, and react at 70-75° C. for 12-16 hours to obtain intermediate 2; Step 3: Mix intermediate 2, diallylmethylamine and carbon tetrachloride in a container, and react at 60-70°C for 6-8h to obtain intermediate 3; Step 4: Mix pyridine, 4-chlorobutene and carbon tetrachloride in a container, and react at 65-75°C for 4-6h to obtain intermediate 4; Step 5: Mix intermediate 3, intermediate 4, diallylmethylamine, tetrasodium ethylenediaminetetraacetate, and deionized water in a container, adjust the pH of the system to 7 with glacial acetic acid, then raise the temperature to 70-75°C, and add tetrasodium ethylenediaminetetraacetate to the container again. After the addition is completed, react at 70-75°C for 3-4 hours to obtain the composite functional agent.

2. The Oxford fabric with high color fastness according to claim 1, characterized in that: The amount ratio of 3,5-dihydroxytoluene, aluminum chloride, carbon tetrachloride and 2-hydroxybenzoyl chloride used in step 1 is 0.1 mol: 22-24 g: 60-80 mL: 0.1 mol.

3. The Oxford fabric with high color fastness according to claim 1, characterized in that: The amount ratio of intermediate 1, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride used in step 2 is 0.05 mol: 0.05-0.07 mol: 5-7 g: 100-120 mL.

4. The Oxford fabric with high color fastness according to claim 1, characterized in that: The amount ratio of intermediate 2, diallylmethylamine and carbon tetrachloride used in step 3 is 0.04 mol: 0.05-0.06 mol: 80-100 ml.

5. The Oxford fabric with high color fastness according to claim 1, characterized in that: The amount ratio of pyridine, 4-chlorobutene and carbon tetrachloride used in step 4 is 0.05 mol:0.05 mol:60-80 mL.

6. The Oxford fabric with high color fastness according to claim 1, characterized in that: The amount ratio of intermediate 3, intermediate 4, diallylmethylamine, tetrasodium ethylenediaminetetraacetate and deionized water used in step 5 is 0.01 mol: 0.01 mol: 0.02-0.03 mol: 0.03 g: 40 g; wherein the ratio of tetrasodium ethylenediaminetetraacetate added for the first time to tetrasodium tetraacetate added for the second time is 1:

2.

7. A method for preparing Oxford fabric with high color fastness, characterized in that: The following steps are involved: The first step: weigh the raw materials according to the mass proportions of PTT fiber 55-68 parts, bamboo charcoal fiber 25-30 parts, silk fiber 15-18 parts, sodium sulfate 5-6 parts, sodium carbonate 0.3-0.5 parts, and composite functional agent 0.6-1.3 parts, make the PTT fiber, bamboo charcoal fiber, and silk fiber into short fibers, and then use a high-speed winding machine to wind the short fibers, and after winding, use a double twisting machine to twist and shrink them for standby use; Step 2: The bobbins that have been shrunk in the first step are warped by a sectional warping machine, and then reeded to weave the Oxford spinning blank; Step 3: dissolving the composite functional agent and sodium carbonate in deionized water to obtain a post-treatment solution; Step 4: The Oxford spun fabric in the second step is put into the dyeing vat after being desized, and sodium sulfate is added to the dyeing vat, and the temperature is continuously raised to complete the dyeing; Step 5: Immerse the dyed Oxford fabric in a post-treatment solution, and dry it after immersion to obtain an Oxford fabric with high color fastness.

8. The method for preparing an Oxford fabric with high color fastness according to claim 7, characterized in that: The winding speed in the first step is 380-460 m / min, and the winding tension is set to 0.06-0.08 N; the twisting speed of the twisting machine is 7800-8600 r / min, and the twisting twist is 6-8 twists / cm.

9. The method for preparing an Oxford fabric with high color fastness according to claim 7, characterized in that: In the second step, the warping speed of the Oxford fabric is 80-120 m / min, the warp density of the Oxford fabric is 90-105 strands / cm, and the weft density is 40-55 strands / cm.

10. The method for preparing an Oxford fabric with high color fastness according to claim 7, characterized in that: In the fourth step, the dyeing temperature condition is 70-90°C, and the dyeing time condition is 30-45min; in the fifth step, the immersion temperature condition is 60-70°C, the immersion time condition is 30-60min, and the drying temperature condition is 130°C.